Direct observation of procedural skills evaluation of suturing skills in surgical interns: A comprehensive analysis - Sangameshwar Patil; Anveer Allad; Jyothi Patil; Pavankumar M Patil (Asian Journal of Medical Sciences, 2024)
Background: The internship period in medical education serves as a critical phase for students transitioning from theoretical learning to practical application within clinical settings. Surgical specialties, in particular, demand a high level of skill and competence from interns due to the inherent risks associated with surgical procedures. However, there is often a gap between the theoretical knowledge gained in medical college and the practical skills required in surgical practice. Aims and Objectives: Therefore, keeping all the above facts in mind, the present study was undertaken to implement direct observation of procedural skills (DOPS) as a method for evaluating the suturing skills performance in interns. Materials and Methods: This study focused on an intern in the Department of Surgery, aiming to assess their suturing skills using the DOPS method. A structured workshop was conducted to provide interns with hands-on training in suturing techniques. Subsequently, interns were divided into groups and assessed by assigned assessors using the checklist. Feedback was provided to interns after each assessment session. Data were collected through self-administered questionnaires distributed to interns and assessors, and statistical analysis was performed using SPSS software. Results: Analysis of the data revealed a significant improvement in suturing skill scores among interns following the implementation of DOPS assessments. Mean scores increased substantially from the initial to subsequent attempts, indicating enhanced proficiency in suturing skills. Interns expressed positive perceptions of the DOPS methodology, highlighting its effectiveness in driving learning and improving confidence in performing surgical procedures. Conclusion: DOPS not only facilitates skill development but also promotes confidence and competence in interns, preparing them for clinical practice. Overall, DOPS emerges as a valuable approach for evaluating and improving suturing skills among interns, contributing to their professional development as competent health-care practitioners.